DINAMIKA PENGGUNAAN BAHASA INDONESIA DAN BAHASA GAUL DI KALANGAN GENERASI MUDA - Mahesti, Anggun; Jaya, Aswadi (Universitas PGRI Palembang, 2024)
This study explores the dynamics of the usage of Bahasa Indonesia and Bahasa Gaul among Indonesian youth. Using a literature review method, the research examines relevant literature to understand how these two languages are interchangeably used in various social contexts. The findings indicate that the youth tend to use Bahasa Indonesia in formal contexts, while Bahasa Gaul is more dominant in informal communication. Factors such as the influence of globalization and social media play a significant role in the spread of Bahasa Gaul. While Bahasa Gaul facilitates the expression of identity and creativity, concerns remain about its impact on the proper use of Bahasa Indonesia. This study highlights the importance of a balanced approach in language education and inclusive language policies to maintain the relevance and integrity of Bahasa Indonesia amidst the evolving social dynamics